The Utilization of Various Plant Type by the Community of Gunung Bunder Dua Village, Bogor Regency as a Resource of Biology Learning Process - Rizna Akmaliyah; Wardah Wardah; Tri Cahyanto; Apriani Krisdianti; Deasy Rahmawati (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
The community of Gunung Bunder Dua Village, Bogor Regency is one area that still has plant knowledge and local wisdom in their daily life. This research aims to reveal the local wisdom of Gunung Bunder Dua villagers, Bogor Regency. The method used in the form of direct observation in the field with interview by selected speaker. This research was conducted from 17th June to 17th July 2019 at the village of Gunung Bunder Dua, Bogor Regency, West Java. The observations recorded were 72 species and 40 plant families, with some varieties of uses, namely 19 species of food plants, 56 species of medicinal plants and 3 species of economic value plants. The  result of this reseach are used as source of biology learning such as a video containing ethnobotany information.Abstrak Masyarakat Desa Gunung Bunder Dua, Kabupaten Bogor termasuk salah satu daerah yang masih memiliki pengetahuan tumbuhan dan kearifan lokal dalam kehidupan sehari-harinya. Penelitian ini bertujuan mengungkap kearifan lokal masyarakat desa Gunung Bunder Dua, Kabupaten Bogor. Metode yang dilakukan berupa observasi langsung di lapangan dengan wawancara kepada narasumber terpilih. Penelitian ini dilakukan dari tanggal 17 Juni – 17 Juli 2019 bertempat di Desa Gunung Bunder Dua, Kabupaten Bogor, Jawa Barat. Terdapat 72 spesies dan 40 famili tumbuhan, dengan beragam kegunaan yaitu tumbuhan pangan 19 spesies, tumbuhan obat 56 spesies, dan tumbuhan bernilai ekonomi sebanyak 3 spesies. Hasil penelitian ini dijadikan sumber belajar biologi berupa video yang berisikan informasi etnobotani.